Mesoporous carbon carrier, preparation method thereof and catalyst for fuel cell
By energizing, activation and calcining the carbon source powder in an inert gas environment, a mesoporous carbon support with a controllable pore structure and high catalytic activity was prepared, which solved the problems of poor pore controllability and complex process of the prior art mesoporous carbon support, and achieved high activity and stability of the catalyst.
Patent Information
- Application Number
- CN202411763538.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
The existing preparation methods of mesoporous carbon support require the help of template methods, resulting in poor pore controllability, difficulty in removing templates, inability to match commercial amorphous carbon, and the process is complicated.
By energizing the carbon source powder in an inert gas environment, a mesoporous structure is formed; the carbon source powder is activated by an oxidant to introduce oxygen-containing functional groups; and graphitizing the carbon source powder through calcination treatment to prepare a mesoporous carbon support with a controllable pore structure and high catalytic activity and stability.
The pore structure of the mesoporous carbon support is well controlled and simple to operate, and the activity and stability of the catalyst are improved. It is suitable for the support of fuel cell catalysts.
Smart Images

Figure CN119528137A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a mesoporous carbon carrier and a preparation method thereof, and a catalyst for fuel cells. Background Art
[0002] Fuel cells are a new type of power generation device with high energy conversion efficiency and green and pollution-free. They can be widely used in fuel cell vehicles, fixed power stations, mobile power sources and other scenarios. The core component of a fuel cell is the membrane electrode, which consists of a catalyst, a proton exchange membrane and a gas diffusion layer. The catalyst has a high cost share, and its activity and stability directly affect the overall performance of the fuel cell.
[0003] Most existing fuel cell catalysts are made of metal (such as Pt) particles supported on carbon carriers. The Pt utilization rate is high, but there is also the undesirable consequence that the activity of Pt in the catalyst layer is reduced due to sulfonic acid coverage and poisoning. To improve such problems, mesoporous carbon can be used as a carrier to encapsulate metal Pt in the mesoporous carbon carrier to avoid direct contact between Pt and polymer and inhibit catalyst poisoning caused by sulfonic acid coverage. At the same time, the combination of mesoporous carbon carrier and metal catalyst with high solid solubility can improve the activity and stability of the catalyst.
[0004] However, at present, the preparation of mesoporous carbon carriers mostly requires the use of template methods. The structure of the carbon carrier depends on the structure of the template. The pore controllability of the prepared carbon carrier is poor, and it is difficult to completely remove the template. The conductivity and specific surface area of the carbon carrier cannot be compared with commercial amorphous carbon, and the preparation process is complicated. Therefore, there is an urgent need for a mesoporous carbon carrier preparation process that can be prepared on a large scale, has a simple method, a controllable pore structure, and is conducive to improving the activity and stability of the catalyst, so as to better match the use requirements of fuel cell catalysts. Summary of the invention
[0005] Based on this, the present application provides a mesoporous carbon carrier and a preparation method thereof, and a catalyst for a fuel cell. The preparation method of the mesoporous carbon carrier is simple to operate, and the pore structure of the prepared mesoporous carbon is controllable, which can make the catalyst have higher catalytic activity and stability.
[0006] The technical solution proposed in this application is as follows:
[0007] According to the first aspect of the present application, a method for preparing a mesoporous carbon carrier is provided, comprising the following steps:
[0008] The carbon source powder is charged and placed in an inert gas environment for an electric treatment so as to electrochemically etch the carbon source powder to form a mesoporous structure;
[0009] Using an oxidant to activate the electrochemically etched carbon source powder, so as to introduce oxygen-containing functional groups on the outer surface of the carbon source powder and the inner surface of the mesoporous structure;
[0010] The activated carbon source powder is calcined to graphitize the carbon source powder to obtain the mesoporous carbon carrier.
[0011] In any embodiment, the power-on process includes a first constant current power-on and a second constant current power-on performed sequentially;
[0012] The current of the first constant current is 2A~10A, the voltage is 2V~15V, the power-on time is 2min~30min, and the power-on mode is direct current, alternating current or pulse;
[0013] The current of the second constant current power supply is 5A~15A, the voltage is 5V~20V, the power supply time is 2min~30min, and the power supply mode is direct current, alternating current or pulse.
[0014] In any embodiment, after the second constant current power supply, the power-on treatment also includes one or more third constant current power supply; the current of the third constant current power supply is 2A~5A, the voltage is 2V~10V, the power-on time is 2min~30min, and the power-on mode is DC, AC or pulse.
[0015] In any embodiment, the interval between two adjacent constant current currents is more than 10 minutes.
[0016] In any embodiment, after the previous constant current electricity is completed and before the next constant current electricity is started, the step of taking out the carbon source powder for reloading is also included.
[0017] In any embodiment, the mesoporous structure includes a first-level pore structure and a second-level pore structure; the pore diameter of the first-level pore structure is d1, 2nm≤d1<5nm; the pore diameter of the second-level pore structure is d2, 5nm≤d2<50nm; the pore volume of the first-level pore structure is 40%~60% of the total pore volume of the mesoporous structure; the ratio of the external specific surface area to the internal specific surface area of the mesoporous carbon carrier is 0.4~0.6:1.
[0018] In any embodiment, the loading of the carbon source powder includes: loading the carbon source powder into an insulating tube with openings at both ends, squeezing the carbon source powder from both ends of the insulating tube so that the resistance of the carbon source powder sample reaches a preset value, and connecting the two ends of the carbon source powder sample to the positive and negative electrodes of a constant current meter, respectively.
[0019] In any embodiment, before the carbon source powder is loaded, the process further comprises: placing the carbon source powder in an alcohol solvent, washing it under ultrasonic conditions, and obtaining the carbon source powder after washing and pretreatment after filtering and drying.
[0020] In any embodiment, the oxidant includes one or more of oxygen, air, hydrogen peroxide and concentrated nitric acid.
[0021] In any embodiment, the activation treatment comprises one or more of hydrothermal reaction, high temperature acid boiling and high temperature calcination.
[0022] In any embodiment, the oxygen-containing functional group includes one or more of a hydroxyl group, a carboxyl group, and an aldehyde group.
[0023] In any embodiment, based on the total mass of the mesoporous carbon support, the mass fraction of the oxygen-containing functional groups is 10% to 20%.
[0024] In any embodiment, the calcination temperature is 400° C. to 900° C., the calcination time is 30 min to 180 min, the calcination atmosphere is an inert atmosphere, and the flow rate of the inert gas is 8 mL / min to 15 mL / min.
[0025] In any embodiment, the carbon source powder includes one or more of conductive carbon black BP2000, conductive carbon black Vulcan XC72, Ketjen black, graphene and carbon nanotubes; and the diameter of the carbon source powder is 5nm~300nm.
[0026] In any embodiment, the G peak intensity of the mesoporous carbon support in the Raman spectrum is IG, the D peak intensity is ID, and 1.2≤IG / ID≤2.5.
[0027] According to the second aspect of the present application, a mesoporous carbon carrier is provided, which is prepared by the preparation method of the mesoporous carbon carrier according to the first aspect of the present application.
[0028] According to the third aspect of the present application, a catalyst for a fuel cell is provided, comprising a carbon carrier and a catalytically active substance loaded on the carbon carrier, wherein the carbon carrier comprises a mesoporous carbon carrier prepared by the preparation method of the mesoporous carbon carrier according to the first aspect of the present application.
[0029] Compared with the traditional technology, this application has at least the following beneficial effects:
[0030] The above-mentioned preparation method of the mesoporous carbon carrier is to form a mesoporous structure inside the carbon source powder by subjecting the carbon source powder to an electric treatment in an inert gas environment, electrochemically etching the carbon source powder; by controlling the process parameters during the electric treatment, mesoporous structures with different diameters can be formed, and the mesoporous structure has good controllability; the carbon source powder is activated by an oxidant, and oxygen-containing functional groups can be introduced on the outer surface of the carbon source powder and the inner surface of the mesoporous structure, which can enhance the interaction between the mesoporous carbon carrier and the catalytically active substance and improve the stability of the catalyst; by calcination treatment, the degree of graphitization of the mesoporous carbon carrier can be controlled. The preparation method has good controllability of the pore structure and is simple to operate. The mesoporous carbon carrier prepared by the method is used as a carrier of a fuel cell catalyst, which can make the catalyst have high catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the process of preparing a mesoporous carbon carrier from a carbon source powder in one embodiment of the present application. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0033] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0035] At present, most of the traditional methods for preparing mesoporous carbon carriers require the use of a template method. The structure of the carbon carrier depends on the structure of the template. The pore controllability of the prepared carbon carrier is poor, and it is difficult to completely remove the template. The conductivity and specific surface area of the carbon carrier cannot be compared with commercial amorphous carbon, and the preparation process is complicated.
[0036] See also Figure 1 In one embodiment of the present application, a method for preparing a mesoporous carbon carrier is provided, the method comprising the following steps:
[0037] Step S10: loading the carbon source powder, and then placing it in an inert gas environment for power-on treatment, so as to electrochemically etch the carbon source powder to form a mesoporous structure inside the carbon source powder;
[0038] Step S20: activating the electrochemically etched carbon source powder with an oxidant to introduce oxygen-containing functional groups on the outer surface of the carbon source powder and the inner surface of the mesoporous structure;
[0039] Step S30: calcining the activated carbon source powder to graphitize the carbon source powder to obtain a mesoporous carbon carrier.
[0040] The above-mentioned preparation method of the mesoporous carbon carrier is to form a mesoporous structure inside the carbon source powder by subjecting the carbon source powder to an electric treatment in an inert gas environment, electrochemically etching the carbon source powder; by controlling the process parameters during the electric treatment, mesoporous structures with different diameters can be formed, and the mesoporous structure has good controllability; the carbon source powder is activated by an oxidant, and oxygen-containing functional groups can be introduced on the outer surface of the carbon source powder and the inner surface of the mesoporous structure, which can enhance the interaction between the mesoporous carbon carrier and the catalytically active substance and improve the stability of the catalyst; by calcination treatment, the degree of graphitization of the mesoporous carbon carrier can be controlled. The preparation method has good controllability of the pore structure and is simple to operate. The mesoporous carbon carrier prepared by the preparation method is used as a carrier of a fuel cell catalyst, which can make the catalyst have high catalytic activity and stability.
[0041] In some embodiments, the power-on process includes a first constant current power-on and a second constant current power-on performed sequentially. The first constant current power-on has a current of 2A to 10A, a voltage of 2V to 15V, a power-on time of 2min to 30min, and a power-on mode of DC, AC or pulse; the second constant current power-on has a current of 5A to 15A, a voltage of 5V to 20V, a power-on time of 2min to 30min, and a power-on mode of DC, AC or pulse.
[0042] By adopting the above-mentioned power-on treatment method, by controlling the process parameters such as the current, voltage and power-on time of the first constant current power supply and the second constant current power supply, the mesoporous structure in the carbon source powder can be effectively regulated to form a multi-level pore structure with different pore diameters in the carbon source powder.
[0043] In some specific examples, a first-level pore structure is formed in the carbon source powder by the above-mentioned first constant current electric current, and the pore diameter of the first-level pore structure is d1, 2nm≤d1<5nm; a second-level pore structure is formed in the carbon source powder by the above-mentioned second constant current electric current, and the pore diameter of the second-level pore structure is d2, 5nm≤d2<50nm; and the pore volume of the first-level pore structure is 40%~60% of the total pore volume of the mesoporous structure; the ratio of the external specific surface area to the internal specific surface area of the mesoporous carbon carrier is 0.4~0.6:1.
[0044] It should be noted that pore volume refers to the pore volume per unit mass of porous solids. It is an important physical quantity that characterizes the pore characteristics of porous materials. Simply put, pore volume is the total volume of pores inside each gram of porous material. Mesopores refer to pores with pore sizes between micropores (pore size less than 2nm) and macropores (pore size greater than 50nm). The pore size of mesopores is generally between 2nm and 50nm. In the field of catalysts, mesoporous materials are excellent catalyst carriers. The presence of mesopores can enable reactants to better contact catalysts, and is also conducive to the diffusion of reaction products, thereby improving catalytic efficiency.
[0045] By controlling the process parameters during the electrical treatment process, the pore structure in the mesoporous carbon carrier can be regulated. For example, the pore size, average pore length, pore volume, etc. of the pore structure can be controlled. This enables the mesoporous structure to confine catalytically active substances (such as metal nanoparticles) and allow water generated during the catalytic process to diffuse from the mesoporous structure to the outside of the mesoporous carbon carrier through gas diffusion, which is beneficial to improving the catalytic activity and stability of the catalyst.
[0046] In some embodiments, after the second constant current current conduction, the current conduction treatment also includes one or more third constant current current conduction; the current of the third constant current current conduction is 2A~5A, the voltage is 2V~10V, the power-on time is 2min~30min, and the power-on mode can be direct current, alternating current or pulse. In this way, combining the first constant current current conduction, the second constant current current conduction and one or more third constant current current conduction can further regulate the mesoporous structure in the mesoporous carbon carrier and form a third-level pore structure. Using the above-mentioned third constant current current conduction process conditions, the pore diameter of the third-level pore structure formed is d3, 50nm≤d3≤80nm.
[0047] In some embodiments, the interval between two adjacent constant current currents is more than 10 minutes. Specifically, the interval between the first constant current current and the second constant current current is more than 10 minutes; the interval between the second constant current current and the third constant current current is more than 10 minutes; and the interval between two adjacent third constant current currents is more than 10 minutes. In this way, the formation of mesoporous structures at all levels is more conducive.
[0048] The first constant current current, the second constant current current and the third constant current current are all constant current processes. In the process of applying electrochemical signals to the carbon source powder sample, the carbon source powder sample will generate heat, its resistance value will change, and the voltage will fluctuate. In this process, the voltage needs to be controlled to be less than 20V to avoid the occurrence of red heat.
[0049] In some embodiments, the carbon source powder may be one or more of conductive carbon black BP2000, conductive carbon black Vulcan XC 72, Ketjen black, graphene and carbon nanotubes; the diameter of the carbon source powder may be 5nm to 300nm. The above types of carbon source powders are widely available and relatively cheap, which can reduce the production cost of the mesoporous carbon carrier.
[0050] In some embodiments, after the previous constant current current is completed and before the next constant current current is started, the step of taking out the carbon source powder for reloading is also included. That is, after the previous constant current current is completed, the carbon source powder is taken out from the carrier, remixed and then loaded into the carrier, and then the next constant current current is performed for electrochemical etching. This arrangement is conducive to changing the contact mode between the carbon source powder particles, so that the electrochemical etching effect of all carbon source powders is more sufficient and uniform.
[0051] In some of the embodiments, loading the carbon source powder includes the following steps: first, loading the carbon source powder into a cylindrical insulating tube with openings at both ends, using two clean cylindrical rods to squeeze the carbon source powder from both ends of the insulating tube to increase the packing density of the carbon source powder and make the resistance of the carbon source powder sample reach a preset value, then removing the cylindrical rods, and then connecting the two ends of the carbon source powder sample to the positive and negative electrodes of the constant current instrument respectively.
[0052] Among them, the material of the cylindrical insulating tube with openings at both ends can be quartz tube, polytetrafluoroethylene tube and other insulating materials. The heat-resistant temperature of the insulating tube needs to be greater than 800°C, the inner diameter of the insulating tube can be 6mm~10cm, the length of the insulating tube can be 5cm~30cm, and the wall thickness of the insulating tube is not limited. The cylindrical rod refers to a cylindrical rod with a diameter consistent with the inner diameter of the selected insulating tube, and the material is polytetrafluoroethylene, graphite or glass. Generally, 1 / 2 of the insulating tube length ≤ the length of the cylindrical rod ≤ the length of the insulating tube.
[0053] In some specific examples, extruding the carbon source powder means applying force to the cylindrical rod manually or mechanically to achieve extrusion of the carbon source powder sample, thereby increasing the bulk density and conductivity of the carbon source powder sample. The carbon source powder sample is visibly compressed from a loose state to a columnar shape to reduce the resistance of the carbon source powder sample. Specifically, after the carbon source powder sample is compressed, its resistance value should be between 1Ω and 5Ω.
[0054] A constant current meter refers to an instrument that can apply an electrical signal to a carbon source powder sample. AC, DC and pulse programs can be set on the constant current meter. The current range of the constant current meter can be 5A~50A, and the voltage range is generally less than 36V. The positive and negative poles of the constant current meter refer to the positive and negative poles of the constant current meter with power supply clamp wires. The power supply clamp is in surface contact with the carbon source powder sample. A cylindrical power supply clamp or an alligator clip can be used. When an alligator clip is used, a cylindrical conductive rod needs to be connected externally. The power supply clamp needs to be cleaned before use to avoid contaminating the carbon source powder sample. The power supply clamp is connected to both ends of the carbon source powder sample so that the electrical signal can be applied to the carbon source powder sample. Specifically, the power supply clamp can be cleaned by wiping it with a cotton ball soaked in anhydrous ethanol.
[0055] In some embodiments, before the power-on treatment, the insulating tube containing the carbon source powder sample is completely exposed to an inert gas environment to eliminate the influence of oxidants such as oxygen on the electrochemical etching process of the sample and prevent the carbon source powder from burning when it contacts the air and overheats. The specific operation is to place the insulating tube in a glove box or a larger quartz tube, or in other enclosed space, so that the atmosphere in contact with the sample is an inert gas, and the type of inert gas can be nitrogen, argon, etc.
[0056] In some embodiments, before the carbon source powder is loaded, the following steps are also included: placing the carbon source powder in an alcohol solvent, washing it under ultrasonic conditions, filtering it, and drying it to obtain the carbon source powder after washing pretreatment. Ultrasonic washing of the carbon source powder by an alcohol solvent can effectively remove impurities on the surface of the carbon source powder and improve the quality of the mesoporous carbon carrier.
[0057] Specifically, the carbon source powder sample can be placed in a beaker filled with alcohol, the ratio of carbon source powder to alcohol can be 1g / 10mL, and then the beaker is placed in a water bath, the temperature is controlled at 25°C~30°C, and the ultrasonic time is controlled at 10min~30min, so as to clean and remove impurities from the surface of the carbon source powder sample.
[0058] Specifically, the alcohol solvent may be ethanol, isopropanol or other alcohol solvents, and the concentration of the alcohol may be 70% to 90%, and the remaining component is deionized water.
[0059] After ultrasonic cleaning, the carbon source powder-alcohol dispersion is first filtered to remove most of the solvent, and then the sample is subjected to rotary evaporation or vacuum drying to remove the remaining solvent. The parameters of the rotary evaporation can be 50°C~60°C, the vacuum degree can be 0.05MPa~0.09MPa, and the parameters of the vacuum drying can be a vacuum oven at 50°C~60°C and a drying time of 20h~30h.
[0060] In some of the embodiments, in the step of activating the electrochemically etched carbon source powder with an oxidant, the oxidant may be one or more of oxygen, air, hydrogen peroxide and concentrated nitric acid. The activation treatment may be one or more of hydrothermal reaction, high-temperature acid boiling and high-temperature calcination. The oxygen-containing functional groups introduced on the outer surface of the carbon source powder and the inner surface of the mesoporous structure after oxidation treatment may be one or more of hydroxyl (-OH), carboxyl (-COOH) and aldehyde (-COH); and, based on the total mass of the mesoporous carbon carrier, the mass fraction of the oxygen-containing functional groups may be 10% to 20%. In this way, it is more conducive to enhancing the interaction between the mesoporous carbon carrier and the catalytically active substance and improving the stability of the catalyst.
[0061] In some specific examples, the hydrothermal reaction is specifically to place the sample in a hydrothermal reactor filled with an oxidant, set the hydrothermal reaction conditions to 150°C~200°C, and the reaction time to 60min~180min. High-temperature acid boiling is specifically to place the sample in a three-necked flask filled with concentrated nitric acid, and place the three-necked flask in an oil bath pot. The ratio of the sample to concentrated nitric acid is 1g / 10mL, and the concentration of concentrated nitric acid is 10%~30%. The reaction conditions are set to 180°C~250°C, and the cooling reflux reaction is 60min~180min. High-temperature calcination is specifically to place the sample in a high-temperature reactor, under air conditions, set the calcination conditions to 200°C~300°C, 60min~180min, and the air flow rate is 8mL / min~15mL / min. In the above-mentioned activation treatment process, oxygen-containing functional groups are grafted onto the outer surface of the carbon source powder and the inner surface of the mesoporous structure.
[0062] Generally, the peaks of carbon and oxygen in the mesoporous carbon support can be tested by XPS and other characterization methods, and then the types and proportions of oxygen-containing functional groups can be determined by peak fitting. The process conditions of the activation treatment can be determined according to the expected types and proportions of oxygen-containing functional groups.
[0063] In some embodiments, the temperature for calcining the activated carbon source powder can be 400°C to 900°C, the calcination time can be 30min to 180min, the calcination atmosphere is an inert atmosphere, and the flow rate of the inert gas can be 8mL / min to 15mL / min. The activated carbon source powder is calcined under the above process parameters to effectively control the graphitization degree of the mesoporous carbon carrier.
[0064] In some embodiments, the calcined mesoporous carbon carrier is characterized by Raman spectroscopy, and the intensity of the G peak and the intensity of the D peak are tested respectively in the Raman spectrum. The intensity of the G peak is represented by IG, the intensity of the D peak is represented by ID, and IG / ID is the degree of graphitization. The degree of graphitization IG / ID of the mesoporous carbon carrier prepared in the present application is 1.2~2.5.
[0065] The mesoporous carbon carrier prepared by the preparation method of the present application has good controllable pore structure, simple preparation method, and good binding property between the mesoporous carbon carrier and the catalytic active substance. The mesoporous carbon carrier is used as a carrier of a fuel cell catalyst, which can make the catalyst have higher catalytic activity and stability.
[0066] The present application will be further described below in conjunction with specific embodiments and comparative examples, but they should not be construed as limiting the scope of protection of the present application.
[0067] Carrier Example 1:
[0068] (1) Take 20g of conductive carbon black BP-2000 as the carbon source powder, put it into a beaker containing 300mL of 70% ethanol, ultrasonicate for 30min, then filter and rotary evaporate at 55℃ to obtain the pretreated sample. Place the pretreated sample in the middle of a cylindrical quartz tube with two open ends. The quartz tube is 20cm long and 5cm in inner diameter. Use two graphite rods with a diameter of 5cm and a length of 6cm to compress the sample. The graphite rods are ultrasonically washed with deionized water and ethanol to remove impurities before use. Insert the two graphite rods into the two ends of the insulating tube respectively, squeeze the carbon powder to increase the packing density of the carbon powder, and remove the graphite rods when the sample resistance reaches 4Ω measured by a multimeter. Use a constant current meter with a range of 30A. The constant current meter leads out the positive and negative electrodes. The chuck is an alligator clip type. The positive and negative electrodes clamp the graphite rods with a diameter of 4cm and a length of 2cm, respectively, and the graphite rods are in contact with the two ends of the sample.
[0069] (2) Place the assembled sample in a glove box, fill it with nitrogen for protection, and then power it on twice. Set the first power-on parameters as: current 3A, voltage 12V, power-on time 10min, power-on mode as DC, perform the first electrochemical etching on the carbon source powder sample to obtain the first-level pore structure. Perform the second power-on with the parameters: current 4A, voltage 16V, power-on time 20min, power-on mode as DC, perform the second electrochemical etching on the carbon source powder sample to obtain the second-level pore structure.
[0070] (3) The sample obtained after the second power-on was placed in a hydrothermal reactor, and 30 mL of 3% hydrogen peroxide solution was added. The hydrothermal conditions were 120°C and 60 min to activate the surface of the carbon carrier to increase the oxygen-containing functional groups on the inner and outer surfaces of the carbon source. The types and proportions of oxygen-containing functional groups were determined by XPS characterization.
[0071] (4) The sample obtained after activation treatment was calcined at 600°C for 1 h in a N2 atmosphere with a N2 flow rate of 8 mL / min to adjust the degree of graphitization and the ratio of oxygen-containing functional groups on the carbon surface to obtain a mesoporous carbon carrier.
[0072] The obtained mesoporous carbon support has a first-order pore structure with an average pore diameter of 3 nm and a second-order pore structure with an average diameter of 20 nm. The external specific surface area / internal specific surface area ratio of the mesoporous carbon support is 0.6. Raman spectroscopy shows that the IG / ID ratio of the material is 2.1, and the total mass fraction of oxygen-containing functional groups is 15wt%, of which the -OH / -COOH ratio is about 40%.
[0073] Carrier Examples 2-4:
[0074] Carrier Examples 2 to 4 are basically the same as Carrier Example 1, except that the conditions of the two electrochemical etchings are different and the carbon surface activation treatment methods are different. The corresponding effect is that the pore size and distribution of the obtained mesoporous carbon carrier, the oxygen-containing functional groups on the mesoporous carbon and the degree of graphitization are different. See Table 1 for details.
[0075] Carrier Comparative Example 1:
[0076] Carrier Comparative Example 1 is substantially the same as Carrier Example 1, except that the carbon source powder after electrochemical etching is not activated. That is, oxygen-containing functional groups are not introduced on the outer surface of the carbon source powder and the inner surface of the mesoporous structure. The parameters are shown in Table 1.
[0077] Table 1
[0078]
[0079] Catalyst Examples 1-4:
[0080] Catalyst Examples 1 to 4 respectively use the mesoporous carbon carriers prepared in Carrier Examples 1 to 4 as carrier materials, and load the catalytically active metal Pt on the carrier materials to obtain Pt / C catalysts, and the Pt loading amount is 10 wt %.
[0081] Catalyst Comparative Example 1:
[0082] In Catalyst Comparative Example 1, the mesoporous carbon carrier in Carrier Comparative Example 1 is used as a carrier material, and a catalytically active metal Pt is loaded on the carrier material to obtain a Pt / C catalyst, and the loading amount of Pt is 10 wt%.
[0083] Catalyst Comparative Example 2:
[0084] In Catalyst Comparative Example 2, conductive carbon black BP-2000 is directly used as a carrier material, and a catalytically active metal Pt is loaded on the carrier material to obtain a Pt / C catalyst, and the loading amount of Pt is 10 wt%.
[0085] Test Method
[0086] (1) Catalytic activity test
[0087] The activity of the catalyst is measured by three-electrode linear sweep voltammetry. First, a certain amount of catalyst powder, solvent, and binder are selected to form a catalyst ink. A certain amount of catalyst ink is dropped on the working electrode of the rotating disk, and the working electrode, reference electrode, and counter electrode are placed in an acidic or alkaline electrolyte solution. Nitrogen is introduced into the electrolyte solution, and a cyclic voltammetric scan is performed after the nitrogen is saturated to activate the catalyst. Then oxygen is introduced into the electrolyte solution, and a linear voltammetric scan is performed after the oxygen is saturated (scanning range 1.2 V~0 V vs RHE, scanning speed 5mV / s), the LSV curve is obtained, and the half-wave potential value is read.
[0088] (2) Stability test
[0089] The stability of the catalyst was evaluated by cyclic voltammetry. First, the initial performance of the catalyst was tested according to the catalyst activity test method. Then, the catalyst was scanned by cyclic voltammetry under oxygen saturation, with a scanning voltage range of 0.6V-1.0V, a scanning rate of 200mV / s, and a scanning number of 10,000. After the scan, a linear voltammetry test was performed, and the stability was evaluated by comparing it with the initial half-wave potential by the half-wave potential difference △E1 / 2. The smaller the value of △E1 / 2, the better the stability; the larger the value of △E1 / 2, the worse the stability.
[0090] The catalytic activity and stability of the Pt / C catalysts in the above catalyst examples and catalyst comparative examples were tested. The test results are shown in Table 2.
[0091] Table 2
[0092]
[0093] It can be seen from Table 2 that the catalyst using the mesoporous carbon carrier of the present application has high catalytic activity and good stability.
[0094] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0095] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the present application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims, and the specification and drawings may be used to interpret the contents of the claims.
Claims
1. A method for preparing a mesoporous carbon carrier, characterized in that: The following steps are involved: The carbon source powder is charged and placed in an inert gas environment for an electric treatment so as to electrochemically etch the carbon source powder to form a mesoporous structure; Using an oxidant to activate the electrochemically etched carbon source powder, so as to introduce oxygen-containing functional groups on the outer surface of the carbon source powder and the inner surface of the mesoporous structure; The activated carbon source powder is calcined to graphitize the carbon source powder to obtain the mesoporous carbon carrier.
2. The method for preparing a mesoporous carbon carrier according to claim 1, characterized in that: The power-on process includes a first constant current power-on and a second constant current power-on performed sequentially; The current of the first constant current is 2A~10A, the voltage is 2V~15V, the power-on time is 2min~30min, and the power-on mode is direct current, alternating current or pulse; The current of the second constant current power supply is 5A~15A, the voltage is 5V~20V, the power supply time is 2min~30min, and the power supply mode is direct current, alternating current or pulse.
3. The method for preparing a mesoporous carbon carrier according to claim 2, characterized in that: After the second constant current power-on, the power-on process also includes one or more third constant current power-on; the current of the third constant current power-on is 2A~5A, the voltage is 2V~10V, the power-on time is 2min~30min, and the power-on mode is DC, AC or pulse.
4. The method for preparing a mesoporous carbon carrier according to claim 3, characterized in that: The interval between two adjacent constant current energizations is more than 10 minutes.
5. The method for preparing a mesoporous carbon carrier according to any one of claims 2 to 4, characterized in that: After the previous constant current electricity is finished and before the next constant current electricity is started, the step of taking out the carbon source powder and reloading is also included.
6. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The mesoporous structure includes a first-level pore structure and a second-level pore structure; the pore diameter of the first-level pore structure is d1, 2nm≤d1<5nm; the pore diameter of the second-level pore structure is d2, 5nm≤d2<50nm; the pore volume of the first-level pore structure is 40%~60% of the total pore volume of the mesoporous structure; the ratio of the external specific surface area to the internal specific surface area of the mesoporous carbon carrier is 0.4~0.6:
1.
7. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The step of charging the carbon source powder comprises: The carbon source powder is loaded into an insulating tube with openings at both ends, and the carbon source powder is squeezed from both ends of the insulating tube to make the resistance of the carbon source powder sample reach a preset value, and the two ends of the carbon source powder sample are respectively connected to the positive electrode and the negative electrode of the constant current instrument.
8. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: Before the carbon source powder is loaded, the method further comprises: The carbon source powder is placed in an alcohol solvent, cleaned under ultrasonic conditions, and filtered and dried to obtain the cleaned pretreated carbon source powder.
9. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The oxidant includes one or more of oxygen, air, hydrogen peroxide and concentrated nitric acid; And / or, the activation treatment comprises one or more of hydrothermal reaction, high temperature acid boiling and high temperature calcination; and / or, the oxygen-containing functional group comprises one or more of a hydroxyl group, a carboxyl group and an aldehyde group; And / or, based on the total mass of the mesoporous carbon support, the mass fraction of the oxygen-containing functional groups is 10% to 20%.
10. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The calcination temperature is 400° C. to 900° C., the calcination time is 30 min to 180 min, the calcination atmosphere is an inert atmosphere, and the flow rate of the inert gas is 8 mL / min to 15 mL / min.
11. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The carbon source powder includes one or more of conductive carbon black BP2000, conductive carbon black Vulcan XC 72, Ketjen black, graphene and carbon nanotubes; the diameter of the carbon source powder is 5nm~300nm.
12. The method for preparing a mesoporous carbon carrier according to any one of claims 1 to 4, characterized in that: The G peak intensity of the mesoporous carbon carrier in the Raman spectrum is IG, the D peak intensity is ID, and 1.2≤IG / ID≤2.
5.
13. A mesoporous carbon carrier, characterized in that: The mesoporous carbon carrier is prepared by the preparation method of any one of claims 1 to 12.
14. A catalyst for a fuel cell, characterized in that: The method comprises a carbon carrier and a catalytically active substance loaded on the carbon carrier, wherein the carbon carrier comprises a mesoporous carbon carrier prepared by the method for preparing a mesoporous carbon carrier according to any one of claims 1 to 12.